Faktor – Faktor Yang Mempengaruhi Implementasi Kebijakan Pengendalian Penyebaran Penyakit Hiv/Aids di Kabupaten Banyuasin - Iriani, Atrika; Sutinah, Sutinah; Taufikqurrohman, Taufikqurrohman (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2022)
This study aims to analyze the factors of communication, human resources, disposition and organizational structure in achieving the results of the implementation of HIV/AIDS disease control policies at the Banyuasin District Health Office, identifying obstacles in implementing policies to control the spread of HIV/AIDS in Banyuasin District. . This research method is experimental, using a qualitative descriptive approach. The unit of analysis in this study is the Banyuasin District Health Office, South Sumatra Province. The selected subjects are (3) people based on the criteria, namely: (1) individuals who understand exactly about HIV/AIDS, (2) individuals who are placed in the Communicable Disease Control room, and (3) individuals who always provide counseling about HIV/AIDS. , with informants to be interviewed, namely: (1) Head of disease control division, (2) Head of disease control section, (3) Health Center doctor, (4) Patient. Data collection techniques are observation, interviews, and documentation. The results of the study can be concluded that the Factors Affecting the Implementation of Policies to Control the Spread of HIV/AIDS in Banyuasin Regency have been running in accordance with the reference to the Minister of Health Regulation No. 21 of 2013 with applicable guidelines and policies.